The clinical value of the Duke Anesthesia Resistance Scale in predicting postoperative delirium after hip fracture surgery: a retrospective study - Yaya Wang; Yan’an Jiang; Huajun Fu; Yikang Zhao; Zhao Xu (PeerJ, 2023)
Aim This study aims to investigate the clinical value of the Duke Anesthesia Resistance Scale (DARS) in predicting postoperative delirium (POD) after hip fracture surgery. Methods A retrospective study was conducted. Clinical data were collected from the patients who had hip fracture and underwent elective total hip arthroplasty in Shaanxi Provincial People’s Hospital, Third Affiliated Hospital of Xi’an Jiaotong University between January 2022 and June 2023. The Consciousness Fuzzy Assessment Scale was used to evaluate the occurrence of POD on postoperative day 3 (POD 3). The enrolled patients were divided into the POD group (n = 26) and the non-POD group (n = 125). Baseline characteristics, surgical data, postoperative information, and laboratory test results were collected. DARS scores were calculated using the minimum alveolar concentration, end-tidal concentration average (ETAC), and bispectral index (BIS). Multivariate logistic regression analysis was conducted to recognize the independent risk factors for POD after hip fracture surgery. Receiver operating characteristic (ROC) curve was plotted to evaluate the value of DARS in POD prediction. Results The average age of POD group was significantly higher, comparing to non-POD group (P < 0.05). DARS scores were statistically lower in the POD group compared to non-POD group (P < 0.05). Multivariate logistic regression analysis found that age and DARS scores were factors impacting post-operative delirium occurrence after hip fracture surgery (P < 0.05). ROC showed that the area under the curve for DARS in predicting POD after hip fracture surgery was 0.929 (95% CI [0.861–0.997]). The optimal cutoff value was 30. The sensitivity was 95.45%, while the specificity was 84.09%. Conclusion DARS score demonstrates good predictive value in hip fracture patients and is feasible in clinical practice, making it suitable for clinical application and promotion.